2007
DOI: 10.1111/j.1399-6576.2006.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐operative recovery profile after laparoscopic cholecystectomy: a prospective, observational study of a multimodal anaesthetic regime

Abstract: Background: Laparoscopic cholecystectomy is now often an ambulatory procedure, but dependent on short-term postoperative complaints of pain and post-operative nausea and vomiting (PONV). The efficacy of post-anaesthesia care units (PACUs) is therefore important to facilitate return to normal functions. We investigated the feasibility and efficacy of a standardized, evidence-based anaesthesia/analgesic regime to identify residual problems in the early post-operative phase. Methods: One hundred and thirty-four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 42 publications
1
34
0
5
Order By: Relevance
“…Ketorolac is the first injectable nonsteroidal antiinflammatory drug used as an analgesic in the perioperative period [1,3,8], it is also used by anestesists like part of the standardized, evidence-based regime [11]. Between all of the NSAIDs, ketorolac is associated with the highest risk estimate of bleeding [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ketorolac is the first injectable nonsteroidal antiinflammatory drug used as an analgesic in the perioperative period [1,3,8], it is also used by anestesists like part of the standardized, evidence-based regime [11]. Between all of the NSAIDs, ketorolac is associated with the highest risk estimate of bleeding [10].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative sedation with midazolam hydrochloride and the routine analgesic regimen (intraoperative diclofenac and acetaminophen with metamizole in the early postoperative period) used in our institution was equivalent and sufficient for all the patients in each group where we did not detect any significant difference between postoperative pain scores. The use of perioperative intravenous narcotics was favored in two recent pediatric series for better compliance but opioids were reported to have serious adverse effects (11,12,20,21). Agarwal and Bagdi (10) used a bilateral subcostal transversus abdominis plane block under ultrasound guidance with similar pain scores to those of our study group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous history of cholecystitis may also contribute to the Oral feeding, postoperative nausea: Although overnight nasogastric drainage was previously favored, we find it unnecessary to keep drainage catheters postoperatively in cases without comorbidities (10,19). In a study of short-term postoperative evaluation of complaints in adults, authors detected a severe postoperative nausea and vomiting (PONV) at a rate of 2% (20). Méndez et al (9) discharged SDD patients after ingestion of clear liquids with no readmission and vomiting but Jawaheer et al (11) reported a high PONV rate of 58% which dropped down to 0% after they changed the type of anesthesia (gaseous to intravenous), and the type of postoperative feeding regime from unrestricted to a light diet for 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…They are, using reduce size trocars, gas insufflation at a lower pressure, use of nitrous oxide in place of carbon dioxide, active evacuation of gas by manual compression or suction or both at the end of the surgery, use of pre-warmed, humid gas instead of cold and dry gas, use of incisional local anaesthetics, use of nonsteroidal anti-inflammatory drugs (NSAIDs),epidural analgesia, multimodal analgesia including prophylactic NSAIDs along with incisional and intraperitoneal local anaesthetics and the use of intravenous lignocaine have been described in an attempt to reduce postoperative pain. 4,3,6 In the present study we have attempted to compare the effect of intraperitoneal and intravenous lignocaine and a combination of both to reduce the postoperative pain and early bowel recovery.…”
Section: Discussionmentioning
confidence: 99%